Chinese Tourists in Sabah, Malaysia: The Mediating Effect of Perceived Value on Destination Quality and Tourist Satisfaction - Qi Qi; Rosazman Hussin; Md Sayed Uddin; Trixie Marjorie Tangit (Macrothink Institute, 2024)
This study aimed to test the potential mediating role of perceived value in the correlation between destination quality and tourist satisfaction. The study tested the mediating effect of perceived value using SPSS-process on a sample of 374 Chinese tourists visiting Sabah from 2017 to 2020. The results demonstrated that the proposed hypotheses were supported. There is a significant positive effect of destination quality on tourist satisfaction. Both dimensions of perceived value, emotional value and economic value have a positive predictive effect on tourist satisfaction. The relationship between destination quality and tourist satisfaction can be moderated by both emotional and economic value. In addition, this research results confirmed that emotional value and economic value had a partial mediating effect. The research indicates that destination managers need to tap into the unique attributes of the destination to enhance service quality. It is also essential to emphasize the perceived value to tourists and to test the quality of the destination by the perceived value, so as to improve the satisfaction of tourists.